Life-history strategies associated to reproduction of three Hyphessobrycon species (Characidae) in lentic environments of upper Paraná River basin - Gonçalves, Cristina da Silva [UNESP]; Souza, Ursulla Pereira; Ferreira, Fabio Cop [UNESP]; Peressin, Alexandre; Braga, Francisco Manoel de Souza [UNESP] (Associação Brasileira de Limnologia, 2013)
AIM: Life-history strategies in fish include essential parameters related to offspring survivorship, fecundity and time of reproduction, which represent adaptive traits that enable a species to deal with spatial and temporal variability of abiotic conditions. This study aimed to compare reproductive traits associated to life-history theory for three Hyphessobrycon species from two lentic environments (four natural oxbow lakes and a man-made reservoir) of Mogi Guaçu River, upper Paraná River basin. METHODS: Specimens were collected with four minnow traps between August 2005 and July 2006 to cover dry and wet seasons (three samples in each season, and three samples in each environment). RESULTS: Reproductive strategy of H. bifasciatus and H. eques, which predominated in the oxbow lakes, differed from H. anisitsi in the reservoir. Hyphessobrycon bifasciatus and H. eques were single spawners with lower fecundity and size at sexual maturity, but invested more in number of eggs per body gram, while H. anisitsi was a multiple spawner species with higher fecundity, larger size at sexual maturity and body size. CONCLUSIONS: In seasonal environments, single spawners are synchronized with the floods to maximize juvenile survivorship, while reservoirs harbors multiple spawners fish due to the reduced fluctuation between high and low floods resulting from dam operation. Therefore, the seasonal condition in the oxbow lakes due to the flood pulse favored single spawners tactic, as showed by H. bifasciatus and H. eques. In contrast, the multiple spawning of H. anisitsi seems to be related to the more stable environmental condition throughout the year provided by the dam. Life-histories reported herein to Hyphessobrycon species must be common to other characid fishes inhabiting similar environments.

OBJETIVO: Em peixes, as estratégias de história de vida incluem parâmetros relacionados com a sobrevivência da prole, fecundidade e período reprodutivo, e representam características adaptativas que permitem uma espécie lidar com a variabilidade espacial e temporal das condições abióticas. O objetivo deste estudo foi comparar as características reprodutivas associadas à teoria da história de vida de três espécies de Hyphessobrycon em dois ambientes lênticos (quatro lagoas marginais naturais e uma represa artificial) do rio Mogi Guaçu, bacia do alto rio Paraná. MÉTODOS: Os exemplares foram coletados com quatro armadilhas do tipo covo entre Agosto de 2005 e Julho de 2006 para abranger as estações seca e chuvosa (três amostras em cada estação e três amostras em cada ambiente). RESULTADOS: A estratégia reprodutiva de H. bifasciatus e H. eques, que ocorreram principalmente nas lagoas marginais, diferiu de H. anisitsi no reservatório. Hyphessobrycon bifasciatus e H. eques foram classificados como desovadores únicos, com fecundidade e tamanho de maturação gonadal menor, mas investiram mais em número de ovócitos por peso corpóreo, enquanto H. anisitsi foi classificado como desovador múltiplo, com fecundidade, tamanho de maturação gonadal e corpóreo maior. CONCLUSÕES: Em ambientes sazonais, os desovadores totais estão sincronizados com o período de inundação para maximizar a sobrevivência da prole, enquanto reservatórios abrigam desovadores múltiplos, devido à flutuação reduzida entre inundações resultante da operação da represa. Dessa forma, a condição sazonal das lagoas marginais devido ao pulso de inundação, favorece a tática reprodutiva dos desovadores totais, como apresentado por H. bifasciatus e H. eques. Ao contrário, a desova múltipla de H. anisitsi parece estar relacionada com a condição ambiental mais estável do ambiente ao longo do ano devido ao represamento. As histórias de vida registradas aqui para as espécies de Hyphessobrycon devem ser comuns para outras espécies de caracídeos que habitam ambientes similares.
Estratégias de história de vida associadas à reprodução de três espécies de Hyphessobrycon (Characidae) em ambientes lênticos da bacia do alto rio Paraná
Keywords: Tetra fishes; Spawning; Fecundity; Body condition; Caracídeos; Desova; Fecundidade; Condição corpórea